Quantitative analysis of Polydatin in a Turkish oak: Quercus coccifera L. with HPLC-DAD - Merve Yüzbaşıoğlu Baran; Didem Şöhretoğlu; Ayşe Kuruüzüm Uz (International Journal of Secondary Metabolite)
In this study, a new, simple, rapid and sensitive HPLC-DAD method was used for analysing polydatin contents of Quercus coccifera (Fagaceae) woody parts extracted with methanol and water. Our results showed that methanol and water extracts of Q. coccifera had high polydatin contents: 14.898±0.147 and 5.574±0.112 mg/g dry extracts, respectively. This is the first developed analytical method for qualitative and quantitative analysis of polydatin in Quercus L. species.